Meeting the Demands: A Review of Best Practices for Online English Language Instruction for IT Diploma Students in Higher Education - Rubiah MOHD YUNUS; Maisarah ARTHUR WAYNE HOUSE (Communications of International Proceedings, 2025)
The rapid growth of the IT sector has amplified demand for graduates with strong English communication skills. Yet many online English courses in higher education are generic and under-contextualized for IT learners, limiting transfer to real technical tasks. This review synthesizes best practices for online English instruction tailored to IT Diploma students, focusing on pedagogy, technology integration, and assessment aligned to authentic IT communication. We systematically scoped (2019–2025) studies on technology-enhanced language learning, task-/project-based approaches, and tools supporting writing, speaking, and collaboration in technical contexts, and conducted a structured narrative review of journal articles and practice reports. Effective courses (i) embed industry-relevant tasks, (ii) blend synchronous collaboration with asynchronous practice, (iii) use adaptive, feedback-rich tools judiciously, and (iv) assess using performance-based rubrics linked to CEFR and technical communication outcomes. Reported gains include improved writing clarity, reduced error density, and higher engagement and retention. This provides implementable design patterns and measurable indicators to help educators adapt courses rapidly. The review informs curriculum designers and instructors seeking scalable, learner-centred, IT-specific online English instruction.
Keywords: Online English instruction; IT Diploma students; Technology-Enhanced language learning.